Answer:
g(-2)=3
g(0)=-5
g(3)=2
Step-by-step explanation:
g(-2)= -2(-2)+ 3(-2) - 5
4-6-5
2-5
g(-2)=3
g(0)= -2(0) + 3 (0)-5
0+0-5
g(0)=-5
g(3)= -2(3) + 3(3)-5
-6+9-5
3-5
g(3)=2
Answer: 14.97 per pair of earrings
Step-by-step explanation:
Yeah C should be the correct answer
You should know that you can predict changes in coordinates after translations without a graph or anything like that.
(x, y) reflected over the x axis = (x, -y)
(x, y) reflected over the y axis = (-x, y)
(x, y) rotated 90 degrees around the origin = (y, -x)
(x, y) rotated 180 degrees around the origin = (-x, -y)
(x, y) rotated 270 degrees around the origin - (-x, y)
So here's our set of points.
A(1, 2), B(4, 6), C(4, 6)
Here's those points reflected over the x axis.
A'(1, -2), B'(4, -6), C'(4, -6)
And here's <em>those</em> points rotated 180° around the origin.
A''(2, -1), B''(6, -4), C''(6, -4)
I think you made a mistake writing down the question, though, because B and C are the same yet you say ABC forms a triangle. You should be able to go through this process with whatever the coordinate was supposed to be.
Inverse operation is an operation that undoes what was done by the previous operation. Take this simple addition problem 5+2=7. If we want to reverse the addition, we just subtract 7-2=5 and we are back where we started. You do the same for multiplication and division.